Undergraduates as course creators: Reflections on starting and sustaining a student-faculty partnership - Spencer, Brooke; Tori, Katerina; Campbell, Robert (International Journal for Students as Partners, 2021)
We reflect on a grassroots partnership to create a new sophomore seminar, “Precision medicine or privileged medicine?” The course puts students in the driver’s seat to explore problems with inclusiveness and quality of biomedical research. It also emphasizes the relevance of “soft skills”, such as emotional intelligence, to build trust, understand inequities and involve patients as partners to improve research. After developing the course, we felt our experience could interest students and faculty interested in pedagogical co-design, especially where this is not supported by a specific initiative. Ours was a multi-year partnership spearheaded by a sophomore, a senior and a volunteer adjunct associate professor. While we made important use of existing university programs, there was no umbrella initiative or overall sponsor to support student-faculty partnerships from first ideas through new course implementation. This meant we operated with both uncertainty and creativity regarding process, continuity and funding. In this essay we reflect on experiences that formed and facilitated our partnership, from our first conversations through course approval. We look at how our partnership became one of pedagogical co-design and shaped an inclusive, real-world problem-oriented course for undergraduates. Our reflections may help students interested in teaching and course development looking to develop relationships with faculty members in which they feel heard and valued. Furthermore, we hope to encourage faculty members looking to create a course that prioritizes student experience, goals, and feedback, through development of collaborative and mutually beneficial partnerships with undergraduates.